Differences in assessments of relative prestige and utility of criminal justice and criminology journals - Williams, Frank P. (American journal of criminal justice, 1995)
Several articles have been written about the relative prestige of journals in criminology and criminal justice. Almost uniformly, however, those rankings have focused on sociology and criminology journals and have generally reflected a sociological orientation. If criminal justice is indeed a separate discipline, such approaches are tantamount to asking psychologists to rate sociological journals within a list of psychology journals. Our approach is first to separate respondents by their degree of identification with criminal justice and their educational orientation. Second, we compile a list of responses to questions about prestige and utility to practitioners across the range of criminal justice and criminology journals. Analyses of these data indicate that there are differences in the way scholars rate journals, based on their identity with criminal justice and their educational orientation. These differences, however, are found in specific journals and in types of journals (i.e., police, corrections, criminal justice) rather than in aggregate perceptions of all criminal justice and criminology journals.